Assessment of Flood Vulnerability Zones in Esan South East LGA, Edo State, Nigeria - Okeke, U. C.; E. J., Ekemezie (Journal of Spatial Information Sciences, 2026)
Flooding remains a major environmental hazard that threatens lives, property, infrastructure, and agricultural activities in many parts of Nigeria. Effective flood risk management requires the identification and mapping of areas that are susceptible to flooding in order to support planning and mitigation efforts. This study assessed flood vulnerability zones in Esan South East Local Government Area, Edo State, Nigeria, using geospatial techniques and multi-criteria decision analysis. The specific objectives were to delineate the spatial distribution of flood-influencing factors, standardize the factors using fuzzy membership functions, determine factor weights through Principal Component Analysis (PCA), and generate a flood vulnerability map using the Weighted Linear Combination (WLC) approach. Five flood-conditioning factors comprising elevation, slope, proximity to drainage networks, proximity to water bodies, and watershed characteristics were derived from geospatial datasets. The factors were standardized using fuzzy membership functions and weighted using PCA before integration through WLC. The resulting flood vulnerability map was classified into Very Low, Low, Moderate, High, and Very High Vulnerability categories. The results showed that proximity to water bodies (22.27%) exerted the greatest influence on flood vulnerability, followed by elevation (20.28%), proximity to drainage networks (20.23%), slope (20.05%), and watershed characteristics (17.17%). The flood vulnerability assessment revealed that 30.69%, 27.22%, 19.07%, 6.33%, and 16.68% of the study area fall within the Very Low, Low, Moderate, High, and Very High Vulnerability classes respectively. Settlement vulnerability analysis identified 49 settlements located within High and Very High Vulnerability zones, with communities such as Asaboro Quarters, Omo Quarters II, Willy Quarters, Udeze Quarters, Ifianyi, Udenka Quarters, Okperu Quarters, Nana Quarters, Emmanuel Quarters, Ekuale Quarters, Odiotor, and Erobobo among those most exposed to flood hazards. The concentration of vulnerable settlements within Emu, Oria, Illushi, and Ewohimii wards highlights the potential threat of flooding to human settlements and socio-economic activities. The study demonstrates the effectiveness of integrating GIS, fuzzy logic, PCA, and WLC techniques for flood vulnerability assessment and provides a scientific basis for flood risk management, land-use planning, and disaster preparedness within Esan South East Local Government Area.